Assessing knowledge and attitudes about end of life: Evaluation of three instruments designed for adults with intellectual disability2. Issue 6 (24th May 2017) - Stancliffe, R. J.; Wiese, M. Y.; Read, S.; Jeltes, G.; Clayton, J. M.
Abstract : Background: This paper examines the development and psychometric characteristics of three instruments about end of life, designed for use with adults with intellectual disability (ID). Respectively, the instruments assess understanding of the concept of death, end‐of‐life planning, and fear of death. Methods: Part 1: instruments were developed or adapted, and pilot tested with 11 adults with ID and 2 disability staff. Part 2: 39 adults with ID and 40 disability staff were assessed on all three instruments. Results: We evaluated comprehensibility, internal consistency, inter‐rater reliability, subscale: total score correlations, missing data, and withdrawal. Psychometric findings were mostly good. Overall, 23% of participants with ID withdrew at some point. This outcome may have been as much due to assessment fatigue as to sensitive content. There were no adverse events. Conclusions: People with ID can reliably complete assessments about end‐of‐life. Generally, each instrument was found to be comprehensible, reliable and valid.